MOLECULAR CLASSIFICATION OF ECHINOCOCCUS GRANULOSUS STRAINS FROM LIVESTOCK ANIMALS IN LIBYA - O. L. Elmajdoub; W. A. Rahman; M.F. F. Wajdii; M. N. Siti Azizah (Российский паразитологический журнал, 2016)
This study demonstrates the distribution of various E. granulosus strains in sheep, cattle and camel. The common sheep strain G1 is mainly found in sheep and cattle, but also parasitized camels. In contrast, the camel strain G6 is found mainly in camels and rarely in sheep and cattle. However, the study also revealed the possible presence of cryptic species that are closely related to both genotypes in livestock of Libya as evident by high mutations in several specimens. Based on the occurrence of overlapping hosts of E. granulosus in Libya, more research on the transmission cycles and genotypes of E. granulosus in Libya is required. In addition, it is suggested that surveys on potential intermediate hosts, including in humans with dogs as the major final host in Libya using higher resolution molecular tools such as microsatellite markers is recommended.